Acorus calamus L. constructed wetland-microbial fuel cell for Cr(VI)-containing wastewater treatment and bioelectricity production. Issue 3 (June 2022) - Liu, Shentan; Qiu, Dengfei; Lu, Feifan; Wang, Yue; Wang, Zuo; Feng, Xiaojuan; Pyo, Sang-Hyun
Abstract: Due to chemical agents consumption and energy demand during traditional Cr(VI)-containing wastewater treatments, it is essential to explore a cost-effective and sustainable technique to remove Cr(VI) from wastewater. Combining of phytoremediation and bio-electrochemical technology, an Acorus calamus L . constructed wetland-microbial fuel cell (CW-MFC) was ingeniously designed to purify Cr(VI)-containing wastewater and harvest bioelectricity, and possible Cr(VI) removal routes were explored. Acorus calamus L. increased the CW-MFC voltage by approximately 69.75%, and maximum power density reached 36.43 mW m −2 . After 9 h, the planted CW-MFC achieved Cr(VI) removal efficiency of 98.92% at an influent Cr(VI) concentration of 12.07 mg/L, while only 76.43% of the Cr(VI) was eliminated in the unplanted CW-MFC. The Cr(VI) removal was achieved mainly through bio-electrochemical reduction and plant uptake, which accounted for 53–67% and 22–33%, respectively. The addition of low concentrations of Cr(VI) improved the CW-MFC power generation, while high levels of Cr(VI) resulted in power decline. The highest maximum power density of 46.63 mW m −2 was observed when influent Cr(VI) concentration was 6.69 mg/L. The CW-MFC's Cr(VI) removal conformed to the first-order reaction kinetics, and a high rate constant of 0.2887 h −1 was achieved even at a Cr(VI) concentration of 18.21 mg/L. The main removal pathway of Cr was associated with cathodic bio-electrochemical reduction of Cr(VI) to Cr(III) and Cr(OH)3 precipitation, and the final fate of Cr was comprehensively analyzed. The obtained research results provide an important reference for the practical application of CW-MFC in Cr(VI)-containing wastewater treatment. Graphical Abstract: ga1 Highlights: Acorus calamus L. of CW-MFC promoted electricity generation and Cr(VI) removal. Promotion and inhibition effects of Cr(VI) concentrations on CW-MFC performance. High first-order Cr(VI) removal rate constant was obtained in the CW-MFC. Cooperation effects of bio-electrochemistry and plant on CW-MFC performance. Cr(VI) removal pathway by the CW-MFC was analyzed.